Steganographic Algorithm in Spatial Domain - Dujan Taha; Ghada Tahir Qasim (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research deals with design and implementation of a new steganographic algorithm to hide secret messages inside digital images. To achieve security to the transmitted messages, a secret key is used to prevent unauthorized persons from extracting these messages. Embedding has been achieved using grey and color images as a cover. Matlab is used to implement the algorithm due to the facilities it provides for dealing with digital images and matrices as well as GUI. Finally, experimental results demonstrate the effieciency of the algorithm in hiding information in imperceptible manner.